The relation of clinical governance climate on quality of care mediated by patient safety culture - Fitriani, Reni; Antonio, Ferdi; Wuisan, Dewi Sri Surya (Intelektual Pustaka Media Utama, 2024)
The hospital organization determines quality of care (QOC) from health services; however, there are many challenges due to the different backgrounds of healthcare workers. Essentially, governance is needed to guarantee a process oriented toward clinical outcomes. Unfortunately, research on clinical management with dimensional measurements conducted in private hospitals is still scanty. This study aimed to investigate the relationship between clinical governance climate (CGC) on QOC mediated by a patient safety culture (PSC) and the control variable adaptation to workload in relation to QOC. Participants were healthcare workers in two private hospitals that have been fully accredited; 416 participants met the requirements. Data were collected by distributing questionnaires in March 2023. Data were analyzed through partial least square – structural equation model (PLS-SEM). The study result indicated a significant positive relationship between CGC and PSC (β=0.851, p-value<0.05). Further, a positive relationship between PSC to QOC (β=0.654, p-value<0.05) was established. However, insufficient evidence indicates a direct relation between CGC on QOC (p-value>0.05). The role of PSC as a full mediating was confirmed (β=0.557, p-value<0.05, CI 95% 0.441-0.677). The finding of this study is the importance of CGC relation to QOC mediated by PSC in private hospitals.